Redefining Cirrhosis – a brief review - Pradhan, SV (Journal of Pathology of Nepal, 2013)
The liver damage is associated with variable amount of fibrosis. The presence of fibrosis with nodule formation is pathognomic of cirrhosis. It is accompanied by vascular remodeling and regeneration with important functional and hemodynamic consequences that include development of portal hypertension and eventually decompensation and death. However fibrosis can regress following successful treatment of the underlying disease. The classification system followed till date does not analyze this aspect. In this brief review the histological features of fibrosis and the newer models for reclassifying cirrhosis is discussed. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9000 Journal of Pathology of Nepal (2013) Vol. 3, 491-496